COUNTRY IMAGE AND BRAND IMAGE IMPACT ON PURCHASING DECISIONS (Third Sector Social Economic Review, 2015)
When consumers want to get some products; country image has an important role in purchasing for these products. As companies follow the market more carefully, users' requests and expectations have gained immense importance with developing technology. Since the main objective of the companies is to make profits, they act strategically by moving their production and assembling centers to advanced countries for the purpose of reducing the costs. Within this process, companies develop the technologies they use and their marketing decisions accordingly to prevent any damage on their brand equity.The aim of this paper, the country's image and brand image impacts show on the buying decision. Analyses have been done about 430 people. Brand image and country image have been investigated on Volkswagen, Toyota, Tofaş-Fiat and, Hyundai; Germany, Japan, Turkey and South Korea; respectively.
Keywords: Country Image; Purchasing Decision; Brand Image